Pengembangan E-Modul Ajar Fisika Bermuatan CHATGPT Pada Materi Gerak Lurus - Fajrin, Moh; Pasaribu, Marungkil; Paramita, Ielda; Santoso, Rudi (Al-Khazini, 2025)
This study aims to determine the process of developing a teaching e-module, its feasibility, and student responses to the use of a teaching e-module containing ChatGPT as a teaching material. The type of research used is Research and Development (R&D) with the ADDIE model, which includes five stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. This study used a questionnaire as the research instrument. The resulting product is an interactive teaching e-module that integrates ChatGPT in learning on straight-lead motion. Validation results by material experts showed an average score of 3.85 (categorized as "very good"), validation by media experts showed an average score of 3.50 (categorized as "very good"), and validation by practitioners (teachers) showed an average score of 3.29 (categorized as "very good"). Limited implementation was conducted with 29 students of grade XI MIPA with an average score of 3.31 (categorized as "strongly agree"). This study concluded that the ChatGPT-based e-learning module is suitable for use as a contextual, effective, and interactive alternative learning material in connecting physics concepts to everyday life, thereby creating more meaningful learning for students.